Augmentation of water pool boiling heat transfer using heating surfaces fabricated by multi passive techniques. (25th January 2023) - Khalaf-Allah, Reda A.; Mohamed, Salwa M.; Saeed, Esraa; Tolan, Mohamed
Highlights: Enhancement nucleate pool boiling heat transfer by creation a new geometric micro-cavity on heating surface using nontraditional Machining. The boiling heat transfer can be enhanced using multi passive techniques. In the present investigation, different geometric micro-cavity created on tested heating surface for boiling pure water at atmospheric pressure. Creating microstructure copper heating surfaces by new modification techniques is the passive technique improve the pool boiling heat transfer coefficient. Improving nucleate boiling heat transfer performance was obtained by applying The microstructure surfaces are fabricated using the wire-cutting machine, laser-processed surface technique, and sandpaper. The nucleate pool boiling heat transfer increased with applying pure water boiled above newly created heating surfaces. In addition, the enhancement percentage increased more by using multi passive techniques for tested heating surface. Abstract: Presenting the findings of an experimental examination of heat transmission during pool boiling on microstructure copper heating surfaces modified in various ways, this paper. The microstructured surfaces are fabricated using the wire-cutting machine, laser-processed surface technique, and sandpaper. Using pure water as the pool boiling liquid, microstructured surfaces' heat transfer coefficients (HTC) are estimated experimentally. The tests are conducted at atmospheric pressure in a saturated pool boiling state with a heat flux ranging from 50 to 580 kW/m 2 . The results showed that a maximum improvement of 51–92 % was obtained using composite surface modification technology by forming a microscopic structure on the surface of the heat source.